A polycarbonate material, its preparation method and use
Patent Information
- Application Number
- CN202511683981.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-17
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-11-17
AI Technical Summary
Traditional polycarbonate materials exhibit selective absorption peaks in the 1064nm/10.6μm laser band, leading to localized overheating and carbonization during laser cutting. Furthermore, ordinary pigments cannot meet the requirements for neutral light filtering, making them unsuitable for high-precision laser cutting.
CuCr2O4 and Cr2O3 are introduced into polycarbonate materials as neutral light-filtering agents. Combined with surface-modified ITO nanowires, lanthanum hexaboride and SiO2-coated ZnO, a network structure is formed to achieve uniform light absorption and heat dissipation, thereby optimizing the laser cutting process.
This technology enables uniform light absorption by the material during laser cutting, avoids local overheating, ensures stable light transmittance, reduces the thickness of the carbonized layer after cutting, and guarantees precise part dimensions.
Smart Images

Figure CN121293708B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer material modification technology, specifically relating to a polycarbonate material, its preparation method, and its application. Background Technology
[0002] Polycarbonate (PC) materials are widely used in automotive headlight covers, ambient lighting panels, and optical components due to their excellent impact resistance, heat resistance, and high transparency (up to 90% transmittance in the visible light band). Neutral density PC, in particular, is suitable for applications requiring neutral light filtering because it maintains the same absorption intensity across the visible light band, ensuring the accuracy of the light source's color. In some applications, due to inherent limitations of injection molding (such as weld lines caused by voids and the need for specific assembly), laser cutting is required after injection molding to further refine the assembly structure of the parts.
[0003] Traditional pure PC materials exhibit selective absorption peaks in the 1064nm / 10.6μm laser band due to their monomer structure, which easily leads to localized overheating during laser cutting. While adding common pigments (such as carbon black) can enhance laser absorption, neutral-filtering PCs have very high requirements for pigments and cannot use ordinary ones. Uneven heat accumulation on the substrate during laser cutting further leads to localized carbonization of the part. In applications such as automotive headlight covers and optical devices, laser cutting requires high precision and a transmittance loss of <5%. Therefore, there is an urgent need to design a polycarbonate material with neutral-filtering properties suitable for laser cutting. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a polycarbonate material, its preparation method, and its application. By designing and screening components, a visible light spectrum neutral absorption layer is constructed in a PC matrix to ensure the neutral light filtering properties of the material. On the other hand, it solves the problem of carbonization caused by local overheating during laser cutting.
[0005] To achieve this objective, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a polycarbonate material, wherein the polycarbonate material comprises the following components in parts by weight:
[0007] 100 parts by weight of polycarbonate
[0008] Neutral filter additive 0.01-0.1 parts by weight
[0009] 0.2-1 parts by weight of surface-modified ITO nanowires
[0010] Lanthanum hexaboride 0.1-0.6 parts by weight
[0011] SiO2 coated ZnO 0.05-0.3 parts by weight.
[0012] The neutral filtering aid comprises a combination of CuCr2O4 and Cr2O3.
[0013] The polycarbonate material provided by this invention, through CuCr2O4 and Cr2O3, achieves neutral light filtering properties in the composite material, ensuring that the light source color is not distorted due to different transmittance at different wavelengths after passing through the material. This allows the polycarbonate material to be used in automotive ambient lighting panels, illuminated logo covers, and front and rear headlights. Surface-modified ITO nanowires uniformly absorb light in the 900-1100nm range, acting as a neutral filter in this wavelength band, while simultaneously forming a network structure for effective heat dissipation, preventing heat concentration during laser cutting. Lanthanum hexaboride can reflect infrared thermal radiation, and SiO2-coated ZnO can scatter photons in the high-temperature region, suppressing the formation of hot spots during laser cutting. The combination of surface-modified ITO nanowires, lanthanum hexaboride, and SiO2-coated ZnO improves the feasibility of laser cutting, effectively reducing the thickness of the carbonized layer after cutting, thereby ensuring the dimensional accuracy of the parts after laser cutting.
[0014] The neutral filter additive is present in amounts of 0.01-0.1 parts by weight, for example, 0.025 parts by weight, 0.028 parts by weight, 0.03 parts by weight, 0.032 parts by weight, 0.035 parts by weight, 0.038 parts by weight, 0.04 parts by weight, 0.045 parts by weight, 0.048 parts by weight, 0.05 parts by weight, 0.055 parts by weight, 0.058 parts by weight, 0.06 parts by weight, 0.062 parts by weight, 0.065 parts by weight, 0.068 parts by weight, 0.07 parts by weight, 0.075 parts by weight, 0.078 parts by weight, 0.08 parts by weight, 0.085 parts by weight, 0.09 parts by weight, 0.095 parts by weight, etc.
[0015] The surface-modified ITO nanowires are present in amounts of 0.2-1 parts by weight, for example, 0.22 parts by weight, 0.25 parts by weight, 0.28 parts by weight, 0.3 parts by weight, 0.32 parts by weight, 0.35 parts by weight, 0.38 parts by weight, 0.4 parts by weight, 0.42 parts by weight, 0.45 parts by weight, 0.48 parts by weight, 0.5 parts by weight, 0.52 parts by weight, 0.55 parts by weight, 0.58 parts by weight, 0.6 parts by weight, 0.62 parts by weight, 0.65 parts by weight, 0.68 parts by weight, 0.7 parts by weight, 0.72 parts by weight, 0.75 parts by weight, 0.78 parts by weight, 0.8 parts by weight, 0.85 parts by weight, 0.9 parts by weight, 0.95 parts by weight, etc.
[0016] The lanthanum hexaboride is present in amounts of 0.1-0.6 parts by weight, for example, 0.12 parts by weight, 0.15 parts by weight, 0.18 parts by weight, 0.2 parts by weight, 0.22 parts by weight, 0.25 parts by weight, 0.28 parts by weight, 0.3 parts by weight, 0.32 parts by weight, 0.35 parts by weight, 0.38 parts by weight, 0.4 parts by weight, 0.42 parts by weight, 0.45 parts by weight, 0.48 parts by weight, 0.5 parts by weight, 0.52 parts by weight, 0.54 parts by weight, 0.56 parts by weight, 0.58 parts by weight, etc.
[0017] The SiO2-coated ZnO is 0.05-0.3 parts by weight, for example, 0.06 parts by weight, 0.07 parts by weight, 0.08 parts by weight, 0.09 parts by weight, 0.1 parts by weight, 0.11 parts by weight, 0.12 parts by weight, 0.13 parts by weight, 0.14 parts by weight, 0.15 parts by weight, 0.16 parts by weight, 0.17 parts by weight, 0.18 parts by weight, 0.19 parts by weight, 0.2 parts by weight, 0.22 parts by weight, 0.24 parts by weight, 0.26 parts by weight, 0.28 parts by weight, etc.
[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0019] As a preferred technical solution, the polycarbonate is optical grade PC with a light transmittance of 86-91% at a thickness of 3mm, for example, it can be 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, etc.
[0020] The polycarbonate material contains ≥98.3% polycarbonate by mass.
[0021] In this invention, the light transmittance of the polycarbonate was obtained according to ISO 13468-2-1999.
[0022] Preferably, the polycarbonate comprises bisphenol A type polycarbonate.
[0023] Preferably, the polycarbonate has a melt index of 10-20 g / 10 min at 300°C and a load of 1.2 kg, for example, 10.5 g / 10 min, 11 g / 10 min, 11.5 g / 10 min, 12 g / 10 min, 12.5 g / 10 min, 13 g / 10 min, 13.5 g / 10 min, 14 g / 10 min, 14.5 g / 10 min, 15 g / 10 min, 15.5 g / 10 min, 16 g / 10 min, 16.5 g / 10 min, 17 g / 10 min, 17.5 g / 10 min, 18 g / 10 min, 18.5 g / 10 min, 19 g / 10 min, 19.5 g / 10 min, etc.
[0024] In this invention, the melt index of the polycarbonate is obtained according to ISO 1133-2012.
[0025] Preferably, the mass ratio of CuCr2O4 to Cr2O3 is (0.5-1.5):1, for example, it can be 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, etc.
[0026] Preferably, the D of CuCr2O4 50 The particle size is 0.1-1.1 μm, for example, it can be 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, 1 μm, 1.05 μm, etc.
[0027] Preferably, the D of the Cr2O3 50 The particle size is 0.3-0.8μm, for example, it can be 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, etc.
[0028] In this invention, the D of CuCr2O4 and Cr2O3 50 The particle size was obtained according to GB / T 29022-2021.
[0029] Preferably, the diameter of the surface-modified ITO nanowires is 15-25 nm, for example, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, etc., and the length is 0.5-2 μm, for example, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, etc.
[0030] Preferably, the aspect ratio of the surface-modified ITO nanowires is (50-80):1, for example, it can be 52:1, 55:1, 58:1, 60:1, 62:1, 65:1, 68:1, 70:1, 72:1, 75:1, 78:1, 80:1, etc.
[0031] In this invention, the method for testing the aspect ratio of the surface-modified ITO nanowires is as follows: the length and diameter of the surface-modified ITO nanowires are measured by SEM scanning electron microscopy, and the length and diameter of the surface-modified ITO nanowires are calculated by applying statistical average values, thereby calculating the aspect ratio.
[0032] Preferably, the surface-modified ITO nanowires are obtained by surface modification of ITO nanowires using a silane coupling agent.
[0033] Preferably, the method for preparing the surface-modified ITO nanowires includes:
[0034] A dispersion was obtained by mixing a silane coupling agent with anhydrous ethanol. ITO nanowires were then immersed in the dispersion for 0.5-2 hours to obtain the surface-modified ITO nanowires.
[0035] The ITO nanowires can be obtained from commercially available products or by self-production. The method for self-producing the ITO nanowires includes: preparing a polystyrene microsphere array on a substrate; modifying the polystyrene microspheres using ICP etching with oxygen; depositing ITO onto the substrate coated with polystyrene microspheres; maintaining the substrate temperature at 280–320°C during ITO deposition to keep the polystyrene microspheres in a molten state; depositing at a deposition rate of 0.08–0.1 nm / s for 15–20 minutes, stopping the deposition, cooling, and removing the substrate; removing residual polystyrene from the ITO-deposited substrate by chloroform immersion or high-temperature annealing to obtain pure ITO nanowires; the ITO nanowires have needle-like tips. Specifically, during ITO deposition, an In:Sn target of 90:10 is used; the vacuum pressure inside the evaporation chamber is less than 5 × 10⁻⁶. -4 Pa. Specifically, the high-temperature annealing process is as follows: annealing is carried out in a rapid annealing furnace at 570-600℃ for 10-15 minutes to remove polystyrene microspheres.
[0036] Preferably, the silane coupling agent comprises γ-(methacryloyloxy)propyltrimethoxysilane and / or γ-aminopropyltriethoxysilane.
[0037] In this invention, surface-modified ITO nanowires can enable polycarbonate materials to absorb light uniformly in the range of 900-1100nm and can form a conductive mesh structure, which can uniformly disperse the heat generated during laser cutting, thereby avoiding local overheating.
[0038] Preferably, the mass percentage of ITO nanowires in the surface-modified ITO nanowires is 90-97%, for example, it can be 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, etc., and more preferably 93-95%.
[0039] Preferably, the D of the lanthanum hexaboride 50 The particle size is 80-120 nm, for example, it can be 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, etc. Lanthanum hexaboride can reflect infrared thermal radiation, thereby reducing laser thermal penetration.
[0040] In this invention, the D of the lanthanum hexaboride 50 The particle size was obtained according to GB / T 29022-2021.
[0041] Preferably, the particle size of the SiO2-coated ZnO is 10-30 nm, for example, it can be 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, etc.
[0042] In this invention, the particle size of the SiO2-coated ZnO is obtained according to GB / T 29022-2021.
[0043] Preferably, the mass ratio of SiO2 to ZnO in the SiO2-coated ZnO is (0.02-0.1):1, for example, it can be 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1, 0.05:1, 0.055:1, 0.06:1, 0.065:1, 0.07:1, 0.075:1, 0.08:1, 0.085:1, 0.09:1, 0.095:1, etc., and more preferably (0.03-0.06):1.
[0044] In this invention, the SiO2-coated ZnO can be prepared by the following method, which includes the following steps:
[0045] (1) ZnO nanoparticles, anhydrous ethanol, and hexadecyltrimethylammonium bromide (CTAB) were mixed to obtain a ZnO dispersion;
[0046] (2) After mixing the ZnO dispersion with ammonia, tetraethoxysilane (TEOS) is slowly added, and then stirred at 60°C for 15-30 h to obtain the SiO2-coated ZnO; the mass ratio of SiO2 to ZnO in the SiO2-coated ZnO is controlled by controlling the amount of ZnO nanoparticles and TEOS added.
[0047] In this invention, the SiO2-coated ZnO can also be prepared by the following method, which includes the following steps:
[0048] Add 0.05 mol / L sodium silicate solution dropwise to a deionized water slurry of ZnO (ZnO mass percentage is 20-30%) to adjust the pH of the slurry to 9.5; continue to add sodium silicate solution dropwise at 85-90℃, control the SiO2 / ZnO (mass ratio) to be (0.02-0.1):1, adjust the pH of the slurry to 8.5 with dilute sulfuric acid, and age for 2-3 hours to obtain the SiO2-coated ZnO.
[0049] Preferably, the polycarbonate material further includes an ultraviolet absorber and / or an antioxidant.
[0050] Preferably, the ultraviolet absorber includes benzotriazole ultraviolet absorbers.
[0051] Preferably, the antioxidant includes hindered phenolic antioxidants and / or phosphite antioxidants.
[0052] Preferably, the ultraviolet absorber in the polycarbonate material is 0.1-1 parts by weight, for example, it can be 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight, 0.5 parts by weight, 0.55 parts by weight, 0.6 parts by weight, 0.65 parts by weight, 0.7 parts by weight, 0.75 parts by weight, 0.8 parts by weight, 0.85 parts by weight, 0.9 parts by weight, 0.95 parts by weight, etc.
[0053] Preferably, the antioxidant in the polycarbonate material is 0.3-1 parts by weight, for example, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight, 0.5 parts by weight, 0.55 parts by weight, 0.6 parts by weight, 0.65 parts by weight, 0.7 parts by weight, 0.75 parts by weight, 0.8 parts by weight, 0.85 parts by weight, 0.9 parts by weight, 0.95 parts by weight, etc.
[0054] Preferably, the polycarbonate material further includes a lubricant.
[0055] Lubricants such as polytetrafluoroethylene have a critical surface tension of only 18-19 mN / m (the lowest among solid materials), making it difficult for molten slag to wet their surface during laser cutting. This effectively prevents the adhesion of carbide slag and further reduces the thickness of the carbide layer during laser cutting.
[0056] Preferably, the lubricant comprises polytetrafluoroethylene.
[0057] Preferably, the lubricant in the polycarbonate material is 0.1-0.5 parts by weight, for example, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight, etc.
[0058] In a second aspect, the present invention provides a method for preparing a polycarbonate material as described in the first aspect, the method comprising:
[0059] The components are melt-blended in proportion and then extruded to obtain the polycarbonate material.
[0060] Preferably, the melt blending temperature is 80-270°C.
[0061] Preferably, the melt blending is carried out in a screw extruder.
[0062] Preferably, the screw extruder includes a twin-screw extruder.
[0063] Preferably, the temperatures of each zone of the twin-screw extruder are as follows: Zone 1: 80-120℃; Zone 2: 120-140℃; Zone 3: 200-220℃; Zone 4: 220-240℃; Zone 5: 250-270℃; Zone 6: 250-270℃; Zone 7: 250-270℃; Zone 8: 230-250℃; and the die head temperature: 240-260℃.
[0064] Preferably, the twin-screw extruder has a screw length-to-diameter ratio of (30-70):1, a screw speed of 200-300 rpm, and a vacuum degree of <-0.08 MPa.
[0065] Preferably, the extrusion process further includes a granulation step.
[0066] Thirdly, the present invention provides the application of the polycarbonate material as described in the first aspect in automotive lamp covers, automotive ambient lighting panels, or optical devices.
[0067] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] The polycarbonate material provided by this invention has neutral light filtering properties and stable transmittance in the 400-1000nm spectral range, ensuring that the light source color is not distorted due to the different transmittance at different wavelengths after passing through the material.
[0070] The polycarbonate material provided by this invention is suitable for laser cutting. After cutting, the thickness of the carbonized layer is effectively reduced, ensuring the accuracy of the part dimensions after laser cutting and the stability of the part dimensions in subsequent assembly. Attached Figure Description
[0071] Figure 1 This is a scanning electron microscope image of the cut edge of the polycarbonate material provided in Example 1 after injection molding and laser cutting;
[0072] Among them, 1-Carbonized layer. Detailed Implementation
[0073] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be considered as specific limitations thereof.
[0074] The sources of some components in the following examples and comparative examples are as follows:
[0075] (1) PC
[0076] PC-1, CLS3400, Mitsubishi, Japan, melt flow index of 14 g / 10 min at 300℃ and 1.2 kg load, light transmittance of 91% at 3 mm thickness;
[0077] PC-2, PC A1220, Wanhua, melt flow index of 20g / 10min at 300℃ and 1.2kg load, light transmittance of 88% at 3mm thickness;
[0078] (2) Neutral filter aid
[0079] Neutral filter aid-1, with a CuCr2O4 to Cr2O3 mass ratio of 0.5:1;
[0080] Neutral filter aid-2, with a CuCr2O4 to Cr2O3 mass ratio of 1:1;
[0081] Neutral filter aid-3, with a CuCr2O4 to Cr2O3 mass ratio of 1.5:1;
[0082] Among them, CuCr2O4, Hunan Kelai, D 50 Particle size 0.7μm; Cr2O3, Xinzhongda, D 50 The particle size is 0.5 μm;
[0083] (3) SiO2-coated ZnO: The preparation method includes: dispersing a certain amount of ZnO nanoparticles (purchased from Jinda, JDGQP-004, with an average particle size of 25 nm, which were subsequently ground twice to obtain ZnO nanoparticles with a particle size of 15 nm) in an appropriate amount of anhydrous ethanol, adding a small amount of surfactant CTAB, ultrasonically treating and mechanically stirring to obtain a uniform and stable ZnO dispersion. Adding an appropriate amount of 0.5 mol / L ammonia water to the dispersion, and then slowly adding a metered amount of TEOS diluted with anhydrous ethanol to the dispersion while stirring vigorously. After the addition of the dispersion, stirring at 60°C for 24 h. After the reaction is completed, filtering and washing repeatedly with anhydrous ethanol and deionized water, and drying to obtain SiO2-coated ZnO; the mass ratio of SiO2 to ZnO in SiO2-coated ZnO is controlled by controlling the amount of ZnO nanoparticles and TEOS added.
[0084] SiO2-coated ZnO-1, SiO2-coated ZnO-2, and SiO2-coated ZnO-3 were prepared according to the above method.
[0085] SiO2 coated ZnO-1, with a SiO2 to ZnO mass ratio of 0.04:1 and a particle size of 15 nm;
[0086] SiO2 coated with ZnO-2, with a SiO2 to ZnO mass ratio of 0.025:1 and a particle size of 15nm;
[0087] SiO2 coated ZnO-3, with a SiO2 to ZnO mass ratio of 0.07:1 and a particle size of 15 nm;
[0088] SiO2 coated ZnO-4, with a SiO2 to ZnO mass ratio of 0.03:1 and a particle size of 25 nm;
[0089] The preparation method of SiO2-coated ZnO-4 is as follows:
[0090] A 0.05 mol / L sodium silicate solution was added dropwise to a deionized water slurry of ZnO (ZnO mass percentage of 25%) to adjust the pH of the slurry to 9.5; sodium silicate solution was added dropwise at 85℃ to control the SiO2 / ZnO (mass ratio) to 0.03:1; the pH of the slurry was adjusted to 8.5 with dilute sulfuric acid; after aging for 2 hours, the SiO2-coated ZnO-4 was obtained by screening.
[0091] (4) Surface-modified ITO nanowires: The preparation method includes: dispersing silane coupling agent (γ-aminopropyltriethoxysilane) with anhydrous ethanol and ultrasonic treatment, immersing ITO nanowires in the dispersion for 1 hour and then taking them out, evaporating the surface solvent to obtain surface-modified ITO nanowires; the mass percentage of ITO in the surface-modified ITO nanowires is controlled by controlling the amount of γ-aminopropyltriethoxysilane and ITO nanowires added.
[0092] The ITO nanowires were prepared using the following method:
[0093] A 2-inch diameter GaN epitaxial wafer was ultrasonically cleaned for 10 minutes at room temperature in a mixed solvent of acetone and 99.7% ethanol, followed by rinsing with deionized water and drying with nitrogen. A single layer of 500 nm diameter polystyrene microspheres was self-assembled and deposited on the cleaned GaN epitaxial wafer, covering the entire wafer. After ICP etching with oxygen for 200 seconds, the GaN epitaxial wafer with the polystyrene microspheres was placed on the sample holder of an electron beam evaporation apparatus, with the polystyrene microsphere side facing the ITO target. After loading the ITO target (In:Sn = 90:10), the evaporation chamber door was closed, and a vacuum was drawn to a pressure less than 5 × 10⁻⁶. -4 Pa was used to heat the target and sample holder to 300℃, causing the polystyrene microspheres to melt. The electron beam spot was adjusted to allow the target material to evaporate and deposit onto the GaN epitaxial wafer. The electron beam current was then adjusted to maintain a deposition rate within the range of 0.08–0.1 nm / s for 15 minutes. After evaporation, the deposition was stopped, and the GaN epitaxial wafer was cooled and removed. The GaN epitaxial wafer with ITO nanowires was then immersed in a chloroform (CHCl3) solution and sonicated for 30 minutes to completely remove the polystyrene microspheres. It was then rinsed with deionized water and air-dried to obtain ITO nanowires with a diameter of 15 nm and a length of 1 μm.
[0094] Surface-modified ITO nanowires-1, with an ITO mass percentage of 90%; diameter of 15 nm and length of 1 μm;
[0095] Surface-modified ITO nanowires-2, with an ITO mass percentage of 93%; diameter of 15 nm and length of 1 μm;
[0096] Surface-modified ITO nanowires-3, with an ITO mass percentage of 97%; diameter of 15 nm and length of 1 μm;
[0097] (5) Lanthanum hexaboride
[0098] Lanthanum hexaboride-1, lanthanum hexaboride purchased from Zhejiang Yamei, was ball-milled to D under a nitrogen atmosphere. 50 After the particle size is reduced to 100nm, it can be used in subsequent applications;
[0099] Lanthanum hexaboride-2, purchased from Zhejiang Yamei, was ball-milled to D under a nitrogen atmosphere. 50 After the particle size is reduced to 120nm, it can be used in subsequent applications;
[0100] (6) Ultraviolet absorber: benzotriazole ultraviolet absorber, UV-234, Tianjin Lianlong New Material Co., Ltd.;
[0101] (7) Lubricant: Polytetrafluoroethylene, POLY TS 30X, PIC (Korea);
[0102] (8) Antioxidants: Phosphite antioxidants, Antioxidant 168, Tianjin Lianlong New Material Co., Ltd.; Hindered phenolic antioxidants, Antioxidant 1076, Tianjin Lianlong New Material Co., Ltd.
[0103] (9) Aniline Black: TN-870, Oriental, Japan, D 50 The particle size is 0.2 μm;
[0104] (10) Surface-modified ITO powder: The preparation method includes: dispersing the silane coupling agent γ-aminopropyltriethoxysilane with anhydrous ethanol and ultrasonic treatment, immersing the ITO powder (purchased from Zhonghang Nano, model ZH-ITO20N, particle size 20nm) in the dispersion for 1 hour and then taking it out, evaporating the surface solvent to obtain the surface-modified ITO powder; the mass percentage of ITO in the surface-modified ITO powder is 90%.
[0105] Example 1
[0106] A polycarbonate material, wherein the polycarbonate material comprises the following components in parts by weight:
[0107] PC-1100 (by weight)
[0108] Neutral filter aid - 10.05 parts by weight
[0109] Surface-modified ITO nanowires - 10.5 parts by weight
[0110] Lanthanum hexaboride - 10.5 parts by weight
[0111] SiO2 coated ZnO-10.1 parts by weight
[0112] Antioxidant 10760.1 parts by weight
[0113] Antioxidant 1680.2 parts by weight
[0114] UV absorber UV-2340.1 parts by weight
[0115] Lubricant POLY TS 30 x 0.1 parts by weight;
[0116] The method for preparing the polycarbonate material includes:
[0117] After pre-drying PC at 120℃ for 4 hours, the above components are mixed evenly in a high-speed mixer and then extruded and granulated using a twin-screw extruder to obtain the polycarbonate material. The twin-screw extruder has a screw length-to-diameter ratio of 40:1, a screw speed of 300 rpm, and a vacuum degree of <-0.08 MPa. The extruder's process conditions are as follows: zone 1 temperature 80℃, zone 2 temperature 120℃, zone 3 temperature 220℃, zone 4 temperature 240℃, zone 5 temperature 270℃, zone 6 temperature 270℃, zone 7 temperature 270℃, zone 8 temperature 250℃, and die head temperature 260℃.
[0118] Examples 2-8, Comparative Examples 1-8
[0119] A polycarbonate material differs from Example 1 only in the type and / or amount (parts by weight) of each component, as shown in Tables 1 and 2. The preparation method of the polycarbonate material is the same as that of Example 1.
[0120] Table 1
[0121]
[0122]
[0123] Table 2
[0124]
[0125] Performance testing:
[0126] The polycarbonate materials provided in the examples and comparative examples were injection molded into square plates with a thickness of 1±0.1 mm using an injection molding machine. The injection conditions were 300°C, 60°C, 30% injection speed, and 25 kPa pressure. The results of the tests are shown in Tables 3 and 4.
[0127] (1) Transmittance: The transmittance of the above square plate was tested using the HunterLab-UltraScan VIS dual-path spectrophotometer from Q-lab, USA.
[0128] (2) Transmittance fluctuation: Transmittance fluctuation = maximum transmittance - minimum transmittance;
[0129] (3) Carbonization layer thickness: The square plate obtained by injection molding of the polycarbonate material provided in Example 1 was laser-cut (wavelength 1064nm). The cutting edge was tested by scanning electron microscopy (Sunlight IS50) to obtain the carbonization layer thickness of the cutting edge and Figure 1 The white area in the image represents the carbonized layer.
[0130] The carbonized layer thickness of other embodiments and comparative examples was tested using the methods described above, and the results are shown in Tables 3 and 4:
[0131] Table 3
[0132]
[0133] Table 4
[0134]
[0135] As shown in Tables 3 and 4, through the design and appropriate ratio of components, the polycarbonate material provided by this invention maintains an almost linear transmittance across all wavelengths in the visible light band, with transmittance fluctuations ≤3.5%, ensuring accurate color reproduction of the light source. Simultaneously, the combined use of surface-modified ITO nanowires, lanthanum hexaboride, and SiO2-coated ZnO reduces the thickness of the carbonized layer formed by heating during laser cutting of the polycarbonate material. The thickness of the carbonized layer is ≤47μm, ensuring the dimensional accuracy of the parts after laser cutting.
[0136] As can be seen from the comparison of Examples 1, 4 and 5, if the mass ratio of SiO2 to ZnO in SiO2-coated ZnO is too small or too large, it will lead to an increase in the thickness of the carbide layer.
[0137] As can be seen from the comparison of Examples 1, 6 and 7, the neutral filtering effect first improves and then deteriorates as the proportion of ITO nanowires in the surface-modified ITO nanowires increases.
[0138] As can be seen from the comparison between Example 1 and Example 8, the lubricant can effectively prevent the adhesion of carbonized slag and further reduce the thickness of the carbonized layer during laser cutting.
[0139] As can be seen from the comparison between Example 1 and Comparative Examples 1-5, the combination of surface-modified ITO nanowires, lanthanum hexaboride, and SiO2-coated ZnO improves the feasibility of laser cutting of the material. The thickness of the carbonized layer after cutting is effectively reduced, thereby ensuring the accuracy of the part size after laser cutting. All three are indispensable.
[0140] As can be seen from the comparative examples of Example 1 and Comparative Example 6, without using SiO2 to coat ZnO, but only physically mixing the two, the thickness of the laser-cut carbide layer is significantly increased.
[0141] As can be seen from the comparison between Example 1 and Comparative Example 7, the thickness of the carbonized layer increases significantly after using surface-modified ITO powder instead of surface-modified ITO nanowires. This is because surface-modified ITO nanowires can form a conductive mesh structure, which can evenly disperse the heat generated during laser cutting, thereby avoiding local overheating. However, surface-modified ITO powder cannot form a conductive mesh structure, leading to local overheating and a significant increase in the thickness of the carbonized layer.
[0142] As can be seen from the comparison between Example 1 and Comparative Example 8, the neutral filtering effect and the thickness of the laser-cut carbonized layer are both very poor when using aniline black instead of a non-central filtering agent.
[0143] The applicant declares that the present invention illustrates the polycarbonate material, its preparation method, and its application through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polycarbonate material, characterized in that, The polycarbonate material comprises the following components in parts by weight: 100 parts by weight of polycarbonate Neutral filter additive 0.01-0.1 parts by weight 0.2-1 parts by weight of surface-modified ITO nanowires Lanthanum hexaboride 0.1-0.6 parts by weight SiO2 coated ZnO 0.05-0.3 parts by weight; The neutral filtering aid is a combination of CuCr2O4 and Cr2O3.
2. The polycarbonate material according to claim 1, characterized in that, The polycarbonate has a light transmittance of 86-91% at a thickness of 3 mm.
3. The polycarbonate material according to claim 1, characterized in that, The polycarbonate has a melt flow index of 10-20 g / 10 min at 300°C and 1.2 kg load.
4. The polycarbonate material according to claim 1, characterized in that, The mass ratio of CuCr2O4 to Cr2O3 is (0.5-1.5):
1.
5. The polycarbonate material according to claim 1, characterized in that, The D of CuCr2O4 50 The particle size is 0.1-1.1 μm.
6. The polycarbonate material according to claim 1, characterized in that, The D of Cr2O3 50 The particle size is 0.3-0.8μm.
7. The polycarbonate material according to claim 1, characterized in that, The surface-modified ITO nanowires have a diameter of 15-25 nm and a length of 0.5-2 μm.
8. The polycarbonate material according to claim 1, characterized in that, The aspect ratio of the surface-modified ITO nanowires is (50-80):
1.
9. The polycarbonate material according to claim 1, characterized in that, The surface-modified ITO nanowires are obtained by surface modification of ITO nanowires using a silane coupling agent.
10. The polycarbonate material according to claim 1, characterized in that, The surface-modified ITO nanowires contain 90-97% ITO nanowires by mass.
11. The polycarbonate material according to claim 10, characterized in that, The surface-modified ITO nanowires contain 93-95% ITO nanowires by mass.
12. The polycarbonate material according to claim 1, characterized in that, The D of the lanthanum hexaboride 50 The particle size is 80-120nm.
13. The polycarbonate material according to claim 1, characterized in that, The particle size of the SiO2-coated ZnO is 10-30 nm.
14. The polycarbonate material according to claim 1, characterized in that, The mass ratio of SiO2 to ZnO in the SiO2-coated ZnO is (0.02-0.1):
1.
15. The polycarbonate material according to claim 14, characterized in that, The mass ratio of SiO2 to ZnO in the SiO2-coated ZnO is (0.03-0.06):
1.
16. The polycarbonate material according to claim 1, characterized in that, The polycarbonate material also includes ultraviolet absorbers and / or antioxidants.
17. The polycarbonate material according to claim 16, characterized in that, The ultraviolet absorber includes benzotriazole ultraviolet absorbers.
18. The polycarbonate material according to claim 16, characterized in that, The antioxidants include hindered phenolic antioxidants and / or phosphite antioxidants.
19. The polycarbonate material according to claim 16, characterized in that, The ultraviolet absorber in the polycarbonate material is 0.1-1 parts by weight.
20. The polycarbonate material according to claim 16, characterized in that, The antioxidant in the polycarbonate material is 0.3-1 parts by weight.
21. The polycarbonate material according to claim 1, characterized in that, The polycarbonate material also includes a lubricant.
22. The polycarbonate material according to claim 21, characterized in that, The lubricant includes polytetrafluoroethylene.
23. The polycarbonate material according to claim 21, characterized in that, The lubricant in the polycarbonate material is 0.1-0.5 parts by weight.
24. A method for preparing a polycarbonate material according to any one of claims 1-23, characterized in that, The preparation method includes: The components are melt-blended in proportion and then extruded to obtain the polycarbonate material.
25. The preparation method according to claim 24, characterized in that, The temperature for melt blending is 80-270℃.
26. The preparation method according to claim 24, characterized in that, The extrusion process also includes a granulation step.
27. The use of a polycarbonate material as described in any one of claims 1-23 in automotive lamp covers, automotive ambient lighting panels, or optical devices.
Citation Information
Patent Citations
Light-tight infrared-transmissive polycarbonate material and preparation method thereof
CN102690508A
PC resin material with neutral filtering effect as well as preparation method and application of PC resin material
CN113801455A
